KONSEP KOALISI PARTAI POLITIK DALAM SISTEM PRESIDENSIAL INDONESIA - Isaliani, Thimoty Pradhitya; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2020)
This study aims to determine the concept of a coalition of political parties in Indonesia and how the juridical implications of political party coalitions in Indonesia in a presidential system. This research is a normative legal research, which is descriptive in nature, which describes precisely the characteristics of an individual, a particular condition, symptoms or groups, or to determine the spread of a symptom, or to determine whether there is a relationship between a symptom and other symptoms in society, in terms of it discusses and describes the concept of political party coalition and the juridical implications of political party coalition in the government system in Indonesia. This study also uses literature study techniques to get answers to these problems. Based on research and discussion, it can be concluded that the coalition of political parties in Indonesia is regulated in Article 6A paragraph 2 of the 1945 Constitution of the Republic of Indonesia that there is room to hold a coalition of political parties as election participants. And in Article 9 of Law Number 42 Year 2008 concerning General Elections of President and Vice President there is a minimum requirement for support to nominate candidates for President and Vice President. The coalition of Indonesian political parties is still inconsistent so that ineffectiveness of government has occurred, so far one factor has juridical implications because the format of political party coalitions in the government system in Indonesia has so far not focused on the similarity of vision and programs and the coalition is still short term.